Stomatognathic System Changes in Obese Patients Undergoing Bariatric Surgery: A Systematic Review (2022)
Background: Obesity is a multifactorial chronic disease involving multiple organs, devices, and systems involving important changes in the stomatognathic system, such as in the orofacial muscles, temporomandibular joint, cheeks, nose, jaw, maxilla, oral cavity, lips, teeth, tongue, hard/soft palate, larynx, and pharynx. Patients with obesity indicated for bariatric surgery reportedly presented with abnormalities in the structures and function of the stomatognathic apparatus. This occurs through the accumulation of adipose tissue in the oral cavity and pharyngeal and laryngeal regions. Therefore, this systematic review aimed to elucidate the changes occurring in the stomatognathic system of patients with obesity after undergoing bariatric surgery. Method: Information was searched based on the equations developed with the descriptors obtained in DECS and MESH using the PRISMA methodology. Studies published between 2010 and October 2021 in databases including PubMed, ProQuest, Scielo, Dialnet, EBSCO, and Springer Link were considered. Results: Eighty articles met the inclusion criteria after evaluating the articles, thereby allowing for the determination of the morphophysiological correlation of the stomatognathic system with the population studied. At the morphological or structural level, changes were observed in the face, nose, cheeks, maxilla, jaw, lips, oral cavity, teeth, tongue, palate, temporomandibular joint, neck, muscles, head, shoulders, larynx, and pharynx. At the morphological level, the main changes occurred in, and the most information was obtained from, the labial structures, teeth, muscles, pharynx, and larynx. Physiological changes were in breathing, phonation, chewing, and swallowing, thereby revealing the imbalance in basic and vital functions. Conclusions: Analyzing the changes and structures of obese patients and candidates for bariatric surgery revealed that, in the preoperative period, the evidence is clear owing to the presence of a wide range of information. However, the information is more limited regarding the postoperative period; thus, further research focusing on characterization of the system postoperatively is warranted.